2009
DOI: 10.1186/1475-2875-8-258
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of Plasmodium falciparum humeral immunity with HIV-1 immunosuppression and treatment efficacy in Zambia

Abstract: BackgroundHIV-1 infection affects malaria humeral immunity during pregnancy, but data for non-pregnant adults are lacking. This study reports the impact of HIV-1 infection and other variables on the level of malaria humeral immunity in adults with clinical malaria and whether humeral immune suppression was a risk factor for treatment failure.MethodsSera of 224 HIV-1 infected and 115 uninfected adults were compared for IgG to merozoite antigens AMA-1 and MSP2 (3D7 and FC27 types) determined by ELISA, and for Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“…These studies have found associations between positive or high IgG responses to a number of antigens (NANP repeat of CSP [39], K1 and MAD20 block 2 variants of MSP-1 [34], MSP-1 19 [32], [33], and GLURP-R0 and R2 [36]) and protection from treatment failure. Three of these studies included assessment of AMA-1 antibodies in their analyses, but these did not show strong associations between anti-AMA-1 levels and clearance of parasitemia [33], [36], [37]. Differences between our results and prior studies may be attributable to the antimalarial therapy used, due to varying efficacy and pharmacokinetics; differences in the epidemiological setting and patient characteristics; different means of assessing treatment outcome; and the use of different laboratory and analytical methods.…”
Section: Discussioncontrasting
confidence: 61%
“…These studies have found associations between positive or high IgG responses to a number of antigens (NANP repeat of CSP [39], K1 and MAD20 block 2 variants of MSP-1 [34], MSP-1 19 [32], [33], and GLURP-R0 and R2 [36]) and protection from treatment failure. Three of these studies included assessment of AMA-1 antibodies in their analyses, but these did not show strong associations between anti-AMA-1 levels and clearance of parasitemia [33], [36], [37]. Differences between our results and prior studies may be attributable to the antimalarial therapy used, due to varying efficacy and pharmacokinetics; differences in the epidemiological setting and patient characteristics; different means of assessing treatment outcome; and the use of different laboratory and analytical methods.…”
Section: Discussioncontrasting
confidence: 61%
“…Likewise, there are a number of confounding factors that also need to be taken into account (e.g. host genetic variation, host immune status) for the absence of antibody responses in some seronegative malaria-exposed subjects [29]. There was, however, no indication of general immune suppression correlated to race or genetic background since antibody responses were induced in malaria-naïve Japanese adults, the majority of seronegative Ugandan adults and young cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis, proliferative and Th1 cytokine responses are reduced in pregnant women with HIV infection, and pregnancy may contribute to impaired control of malaria in HIV-infected individuals [ 8 ]. However, variant surface antigen antibody levels, which seem important for the control of parasite density and treatment outcome, seem to be marginally or not affected by HIV-1 in non-pregnant adults [ 9 ]. In pregnancy, although antimalarial antibody responses are mostly unaltered, there seem to be impaired responses to some antigens, including variant surface antigens expressed on infected erythrocytes binding chondroitin sulfate A, a key receptor for placental sequestration.…”
Section: Pathophysiologymentioning
confidence: 99%